Effects of Higher CO2 and Temperature on Exopolymer Particle Content and Physical Properties of Marine Aggregates - Cisternas-Novoa, Carolina; Lee, Cindy; Tang, Tiantian; de Jesus, Roman; Engel, Anja (Frontiers in Marine Science, 2019)
We investigated how future ocean conditions, and specifically the interaction between temperature and CO2, might affect marine aggregate formation and physical properties. Initially, mesocosms filled with coastal seawater were subjected to three different treatments of CO2 concentration and temperature: 1) 750 ppm CO2, 16°C, 2) 750 ppm CO2, 20°C, and 3) 390 ppm CO2, 16°C. Diatom-dominated phytoplankton blooms were induced in the mesocosms by addition of nutrients. In aggregates produced in roller tanks using seawater taken from the mesocosms during different stages of the bloom, we measured sinking velocity, size, chlorophyll a, particulate organic carbon and nitrogen, and exopolymer particle content; excess density and mass were calculated from the sinking velocity and size of the aggregates. As has been seen in previous experiments, no discernable differences in overall nutrient uptake, chlorophyll-a concentration, or exopolymer particle concentrations could be related to the acidification treatment in the mesocosms. In addition, in the aggregates formed during the roller tank experiments, we observed no statistically significant differences in chemical composition among the treatments during Pre-Bloom, Bloom, and Post-Bloom periods. However, physical characteristics were different and showed a synergistic effect of warmer temperature and higher CO2 during the Pre-Bloom period; at this time, temperature had a larger effect than CO2 on aggregate sinking velocity. In roller tank experiments with warmer and acidified treatment (future conditions), aggregates were larger, heavier and settled faster than aggregates formed at present-day or only acidified conditions. During the Post Bloom, however, aggregates formed under present and future conditions had similar physical properties. In acidified tanks at ambient temperature, aggregates were slower, smaller and less dense than those formed at the same temperature but under present CO2 or under warmer and acidified conditions. Thus, the sinking velocity of aggregates formed in acidified tanks at ambient temperature was slower than the other two cases. Our findings point out the potential of ocean acidification and warming to modify physical properties of sinking aggregates but also emphasize the need of future experiments investigating multiple environmental stressors to clarify the importance of each factor.